Aerobic Training and Circulating Neurotrophins in Alzheimer's Disease Patients: A Controlled Trial. Issue 1 (1st January 2023) - Stein, Angelica Miki; Coelho, Flávia Gomes de Melo; Vital-Silva, Thays Martins; Rueda, André Veloso; Pereira, Jessica Rodrigues; Deslandes, Andréa Camaz; Camarini, Rosana; Santos Galduróz, Ruth Ferreira
ABSTRACT: Objective: to verify the effects of aerobic exercise training in circulating BDNF, VEGF165 and IGF-1 plasma levels and cognitive function in Alzheimer's Disease (AD) patients. Methods: 34 AD patients participated in the study, divided in two groups: Control Group (CG; n = 16) and Training Group (TG; n = 18 – Moderate aerobic training on the treadmill, three times a week, for 12 weeks). BDNF, VEGF165, and IGF-1 plasma levels were considered as a primary outcome. Secondary outcomes included cognitive functions and aerobic fitness. Results: After 12 weeks, maintenance of executive functioning in the TG was found, yet no significant changes on circulating neurotrophins levels were identified. For aerobic fitness, there was an increment in TG group. Conclusion: Twelve weeks of aerobic training were neither effective in improving cognitive functioning significantly, nor influential on circulating neurotrophins levels in AD patients.